EMERGING POTENTIAL OF PLANT DYES AS THERAPEUTIC AGENTS - BUSHRA KHANAM; RAMESH CHANDRA (International Journal of Pharma and Bio Sciences, 2015)
Plant biodiversity of India is rich and abundant wealth of functional germplasm resources and plant kingdom is a treasure-house of various natural products. Dyes are one of the natural products obtained from plants. In recent years, interest in the use of natural dyes has been growing rapidly due to stringent environment standards enforced by many countries due to side effects like, allergic and toxic reactions caused by synthetic dyes, worldwide demand of natural dyes has increased due to awareness on therapeutic properties of plant based dyes. The structure and functional properties of natural dyes have been identified in the recent past. Some dyes extracted from plants have important medicinal properties like; antimicrobial activities, antifungal activities. The present review, describes the detailed information about the chemistry of the major pigments and their medicinal importance of following dye producing plants, these efforts can be helpful for further development of pharmaceutical formulations.